ASSESSMENT OF THE CONDITION OF THE DISTRIBUTION ELECTRICALNETWORK WITH DIFFERENT COMPLETENESS OF INPUT DATA - BURYKIN, OLEKSANDER; MALOHULKO, YULIYA; TOMASHEVSKIY, YURII; SHCHERBATYI, DANYLO (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The most effective measure to ensure the observation of electric distribution networks is the integration of intelligent metering devices with the ability to store and transmit data based on Smart Metering technology into automated commercial electricity metering systems. Automated systems of commercial electricity metering systems and intelligent metering devices are designed to provide reliable and timely information about electricity metering on the basis of which financial settlements are made between market participants. However, today the use of automated systems of commercial electricity metering of intelligent metering devices in distribution networks is limited, and the available information does not make it possible to ensure the observation of electric distribution networks and, as a result, to determine the components of electricity losses in the structure of the electricity balance with sufficient accuracy. That is why the article analyzes the possibility of improving the observability of electrical distribution networks using Smart Metering devices. The expediency of applying the results of assessing the state of distribution electric networks in information systems for the purpose of detailed analysis of the functioning of electric networks is investigated. A mathematical model for assessing the state of the distribution electrical network and the quality of measurements in it is applied. Smart Measuring Information Systems accumulate information about measured power consumption schedules, the use of which allows to form an element-by-element structure of electricity losses with reference to the time period of operation of network elements, as well as determine local cells with the greatest impact on total electricity losses. In addition, commercial expenses included in the balance sheet structure do not have an independent mathematical description. Therefore, it is difficult to assess their economically justified level. They are determined from the structure of the electricity balance, as the difference between actual losses and calculated technological losses. An increase in the profit of energy supply companies depends on the reduction of the commercial component. Thus, the urgent task is to develop methods and tools for analyzing technical and commercial electricity losses in electric distribution networks and introduce software tools for their implementation using Smart Metering databases and Information Systems.